Optogenetic inactivation of the entopeduncular nucleus improves forelimb akinesia in a Parkinson's disease model - Yoon, Hyung Ho; Nam, Min-Ho; Choi, Il; Min, Joongkee; Jeon, Sang Ryong (ELSEVIER, 2020)
We performed optogenetic inactivation of rats' entopeduncular nucleus (EP, homologous to primates' globus pallidus interna (GPi)) and investigated the therapeutic effect in a rat model of PD. 6-Hydroxydopamine (6 - OHDA)-induced hemiparkinsonian rats were injected with either a virus for halorhodopsin expression that is used to inactivate GABAergic neurons or a control virus injection and received optic fiber insertion. All the rats were illuminated by 590 nm of light. Each rat was then subjected to sequential sessions of stepping tests under controlled illumination patterns. The stepping WA is a reliable evaluation method for forelimb akinesia. The number of adjusting steps was significantly higher in experimental (optogene with reporter gene expression) (5Hz - 10ms: 15.7 +/- 1.9, 5Hz - 100ms: 16.0 +/- 1.8, continuous: 21.6 +/- 1.9) than control rats (reporter gene expression) (5Hz-10ms: 1.9 +/- 1.1, 5Hz-100ms: 2.6 +/- 1.0, continuous: 2.5 +/- 1.2) (p < 0.001). Continuous EP illumination showed a significantly higher improvement of forelimb akinesia than other illumination patterns (p < 0.01). Optogene expression in the GABAergic neurons of the EP was confirmed by immunohistochemistry. Optogenetic inhibition of EP was effective to improve contralateral forelimb akinesia. However, further studies using prolonged illumination are needed to investigate the best illumination pattern for optogenetic stimulation.
Keywords: DEEP-BRAIN-STIMULATION; RAT MODEL; NEURONAL-ACTIVITY; BASAL GANGLIA; LEVODOPA